2021
DOI: 10.33716/bmedj.1007824
|View full text |Cite
|
Sign up to set email alerts
|

Foreign body aspiration in children: A survey based study

Abstract: Aim: Foreign body aspiration (FBA) is a life-threatening emergency that causes airway obstruction. This study aims to investigate the amount of awareness there is about the life-threatening emergency FBA among Turkish mothers who are full-time carers of their children, and to provide these mothers with information regardless of their answers. Material and Method: 1034 mothers with children between 6 months and 5 years old were included in the study. Participants were asked to provide their sociodemographic inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 23 publications
2
2
0
Order By: Relevance
“…Regarding symptoms of foreign body aspiration, present study shows that about 89.3% recognized difficulty breathing ,70.2% difficulty talking, 50.0% choking and 16.7% coughing as a symptom of FBA however the study conducted in Qassim, Saudi Arabia shows different result that only 33% responded difficulty breathing, 44.7% difficulty talking, 19.5% choking, 10.4% coughing as a symptom of FBA 1 . Majority of the respondents (86.9%) stated that swallowing foreign body is lethal similar to the study conducted in Turkey that stated 77.47% response for swallowing foreign body is lethal 11 . The present study depicts that 47.6% respondents responded that continuous supervision of child as a preventive measure of FBA, followed by avoid giving high risk foods such as nuts, seeds, small fruits i.e.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Regarding symptoms of foreign body aspiration, present study shows that about 89.3% recognized difficulty breathing ,70.2% difficulty talking, 50.0% choking and 16.7% coughing as a symptom of FBA however the study conducted in Qassim, Saudi Arabia shows different result that only 33% responded difficulty breathing, 44.7% difficulty talking, 19.5% choking, 10.4% coughing as a symptom of FBA 1 . Majority of the respondents (86.9%) stated that swallowing foreign body is lethal similar to the study conducted in Turkey that stated 77.47% response for swallowing foreign body is lethal 11 . The present study depicts that 47.6% respondents responded that continuous supervision of child as a preventive measure of FBA, followed by avoid giving high risk foods such as nuts, seeds, small fruits i.e.…”
Section: Discussionsupporting
confidence: 67%
“…Regarding first aid management in the present study majority of the respondents 81.0% identified immediate management by dislodging airway as a first aid management. The present study shows that majority of the respondent (84.5%) responded that first aid should be initiated within 4 minutes which is similar to research conducted in Turkey with 85.76% response11 . Only 23.8% responded starting CPR if victims become unresponsive as a management which is contradictory to a study conducted in western region Saudi where 48.9% responded starting CPR if victim becomes unresponsive as a management…”
supporting
confidence: 87%
“…These findings align with the outcomes of three related studies conducted in both Turkey and Saudi Arabia, emphasizing the existence of elevated knowledge levels among individuals with higher educational backgrounds. 25 , 26 , 29 Nevertheless, it is important to acknowledge that a study conducted in Dammam city, Saudi Arabia, did not identify any substantial disparities in choking-related knowledge between participants who had completed high school and those who had attained a college-level education. 28 …”
Section: Discussionmentioning
confidence: 98%
“…Several studies conducted in various countries, including Saudi Arabia, Turkey, Ethiopia, and Japan, have explored awareness and knowledge related to choking. 23 33 Our literature review revealed a widespread lack of knowledge about choking in many countries. Notably, a study conducted in Saudi Arabia revealed that 61.3% of parents in the Al Qassim region and 65.4% of parents in Makkah possessed inadequate knowledge regarding choking, with 55.3% of parents in Al Qassim and 78.6% of parents in Makkah exhibiting unsatisfactory practices.…”
Section: Introductionmentioning
confidence: 99%